A brief report of the Orthoptera expedition in the Amazon basin and the Andes of southern Ecuador - Castillo, Elio Rodrigo Daniel (2022)
Fauna and flora of Ecuador are among the most diverse and magnificent in the New World. Because the Andean Cordillera’s rise was relatively recent and complex, a great number of speciation events occurred in this area, most likely as a result of dispersion and vicariance. The Ecuadorian fauna is extremely rich and diversified, which is one of the key repercussions of these events. In this South American region, biological research consistently produces excellent and new data, not just in taxonomy but also in evolutionary biology, speciation studies, biogeography, and other relevant fields. Across the entire expedition, a total of 840 individuals of Orthoptera were collected. At least half of the specimen records correspond to new distributions and some species found will be added to the current list of Ecuadorian Orthoptera. We also believe that some of them correspond to species not yet described. This trip was ambitious and also a challenging task because, in that moment, COVID-19 cases in Ecuador were multiplying daily and restriction of physical contact to prevent the spread of the disease was strict. Additionally, the last collections in Ecuador for several grasshopper groups were made more than 15 years ago (e.g., Jivarus and Quitus species), so we did not know the impact of human activities (or others) in their distribution.